2010
DOI: 10.4049/jimmunol.0804279
|View full text |Cite
|
Sign up to set email alerts
|

Differential but Direct Abolishment of Human Regulatory T Cell Suppressive Capacity by Various TLR2 Ligands

Abstract: CD4+CD25high regulatory T cells (Tregs) control cellular immune responses and maintain peripheral tolerance. We investigated whether TLR2 ligands are able to abrogate Treg-induced suppression in humans based on different reports about effects of triacylated lipopeptide Pam3CSK4 in mice. Pretreatment of human Tregs with a mixture of TLR2 ligands Pam2CSK4, FSL-1, and Pam3CSK4 reduced the Treg-mediated suppression of CD4+CD25− responder T cells in the majority of the analyzed donors. Differential effects of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
51
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 46 publications
9
51
2
Order By: Relevance
“…Recent evidence suggests that TLRs are involved in controlling Treg functions (3,4). Previous reports in murine and human cells demonstrated that TLR2 ligation leads to reduced suppressive function of Tregs (4, 10, 11), even when combinations of various TLR2 agonists are used (10). We examined the effect of Pam3Cys and FSL-1 separately on the suppressive functions of magnetic bead-isolated and FACS-sorted Tregs.…”
Section: Tlr2 Stimulation Reduces the Suppressive Functions Of Tregsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent evidence suggests that TLRs are involved in controlling Treg functions (3,4). Previous reports in murine and human cells demonstrated that TLR2 ligation leads to reduced suppressive function of Tregs (4, 10, 11), even when combinations of various TLR2 agonists are used (10). We examined the effect of Pam3Cys and FSL-1 separately on the suppressive functions of magnetic bead-isolated and FACS-sorted Tregs.…”
Section: Tlr2 Stimulation Reduces the Suppressive Functions Of Tregsmentioning
confidence: 99%
“…ZaninZhorov et al (12) showed that HSP60 increased Treg suppressive function, and its effects led to activation of signaling molecules PKC, PI3K, and p38. By contrast, recently Oberg et al (10) showed that a mixture of synthetic lipopeptides including Pam3-Cys, FSL-1, and Pam2Cys enhances AKT phosphorylation and reduces Treg function. In fact, a reduced AKT phosphorylation and decreased activation of S6 and FOXO pathways is required for the suppressive function of Tregs (13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…74 For example, both Vd2 75 and Vd1 76 cd-T cells can be activated by TLR4 and TLR5 ligands and exhibit increased antibacteria responses, whereas the specific expression of TLR3 in Vd2 cd-T cells favors their stimulation through this pathway. 74 Moreover, pan-cd-T cells can be activated 77 through stimulation of the heterodimers TLR1/2 and TLR2/6 with a mixture of TLR2 ligands, while the production of Th1 cytokines and the cytolytic activity of cd-T cells can be enhanced by stimulation with double-stranded RNA 78 and DNA 79 through TLR3 and TLR9, respectively, during viral infections.…”
Section: Host Cell-derived Signalsmentioning
confidence: 99%